Incorporation of probiotic bacteria in whey cheese: decreasing the risk of microbial contamination - Madureira, A. R. (2013)
For dairy products that are consumed fresh, contamination by spoilage microorganisms and pathogens from the environment is a major concern. Contamination has been associated with a number of outbreaks of foodborne illnesses; however, consistent data pertaining to the microbial safety of whey cheeses specifically have not been reported. Hence, the goals of this research effort were (i) to manufacture a probiotic whey cheese with Bifidobacterium animalis and Lactobacillus casei and (ii) to assess the antimicrobial activity of these probiotics against a set of foodborne pathogens (Listeria innocua, Salmonella Enteritidis, and Staphylococcus aureus) and food spoilage microorganisms (Pseudomonas aeruginosa and Escherichia coli). Three ranges of these microbial contaminants were used for inoculation of cheeses: 103 to 104, 104 to 106, and 106 to108 CFU/g. Inoculation in plain culture medium served as a control. The inhibition produced by the probiotics was calculated, and the major effect was found to be bacteriostatic. In specific cases, full inhibition was observed, i.e., by B. animalis against P. aeruginosa and by L. casei against Salmonella Enteritidis and L. innocua. Conversely, the least inhibition was detected for L. casei against P. aeruginosa. Our results suggest that use of these probiotic strains can extend the shelf life of whey cheeses and make them safer by delaying or preventing growth of common contaminant bacteria.